The Emerald guide to C. Wright Mills - Treviño, A. Javier (Emerald Publishing Limited, 2021)
This book offers a comprehensive guide to reading and understanding the development of Mills's sociological ideas, placing them in the context of his life and his position in American sociology. The Emerald Guide to C. Wright Mills focusses on his concern with the interrelationship between social structure and personality, and with the bureaucratisation of modern society and the power relations it produces. The book takes a chronological and biographical approach in illustrating the development of Mills's ideas and interests over the course of his career. In doing so, it reveals the consistency as well as the evolution of his thinking. Essential reading for students and those new to Mills's ideas, this is a readable, clear, and comprehensive overview of the work of C. Wright Mills, and conveys his influence on contemporary social thought.
Includes index.
Keywords: Mills, C. Wright -- (Charles Wright), -- 1916-1962.; Sociology.; Social sciences -- Philosophy.; Social Science -- Sociology / Social Theory.; Social theory.; elektronické knihy; electronic books